Copper and magnesium - doped zinc oxide nanorods for device applications - Lupan, O.; Sontea, V.; Railean, S.; Pocaznoi, I.; Chow, L. (Видавництво Львівської політехніки, 2012)
In this paper we present an experimental approach to study copper and magnesium-doped zinc oxide nanorods and their integration in wavelength-tunable light-emitting diodes (LEDs).
Keywords: Nanorod; zinc oxide; deposition bath; lightemitting diodes